Acute myocardial infarction in the elderly: Treatment strategies and 28‐day‐case fatality from the MONICA/KORA myocardial infarction registry. Issue 4 (2nd September 2015) - Amann, Ute; Kirchberger, Inge; Heier, Margit; von Scheidt, Wolfgang; Kuch, Bernhard; Peters, Annette; Meisinger, Christa
Abstract : Objectives: Aim of this observational study was to analyze today's real‐life treatment strategies in elderly patients with an acute myocardial infarction (AMI) and to assess the association between 28‐day‐case fatality and invasive strategy (percutaneous coronary intervention/coronary artery bypass grafting). Background: Elderly patients increasingly constitute a large proportion of the AMI population. Methods: The present study is an analysis of all patients aged 75–84 years, who were enrolled in the German population‐based MONICA/KORA MI registry between 2009 and 2012 and who were defined as nonfatal at least 24 hours surviving AMI cases according to MONICA definition. Multivariable logistic regression analyses were conducted for the total study population and stratified by type of AMI (ST‐segment elevation MI [STEMI], Non‐ST‐segment elevation MI [NSTEMI], and bundle branch block [BBB]). Results: Out of the 1, 191 elderlies, 61.9% were treated invasively. In the multivariable analysis, the odds ratio (OR) for 28‐day‐case fatality in patients treated with invasive versus conservative strategy was 0.43 (95% CI 0.27–0.69). Stratified analyses revealed an OR of 0.27 (95% CI 0.13–0.56) for patients with NSTEMI. In patients with STEMI or BBB also a positive trend for invasive strategy was observed (OR 0.40; 95% CI 0.13–1.27 and OR 0.76; 95% CI 0.16–3.66, respectively). Conclusions: Invasive revascularization therapy was independently associated with short‐term survival in elderly patients, particularly in those with NSTEMI. © 2015 Wiley Periodicals, Inc.